Rapid and differential regulation of AMPA and kainite receptors at hippocampal mossy fibre synapses by PICK1 and GRIP - Dev, Kumlesh (My University, 2003)
We identified four PDZ domain-containing proteins, syntenin, PICK1, GRIP, and PSD95, as interactors with the kainate receptor (KAR) subunits GluR52b, GluR52c, and GluR6. Of these, we show that both GRIP and PICK1 interactions are required to maintain KAR-mediated synaptic function at mossy fiber-CA3 synapses. In addition, PKCα can phosphorylate ct-GluR52b at residues S880 and S886, and PKC activity is required to maintain KAR-mediated synaptic responses. We propose that PICK1 targets PKCα to phosphorylate KARs, causing their stabilization at the synapse by an interaction with GRIP. Importantly, this mechanism is not involved in the constitutive recycling of AMPA receptors since blockade of PDZ interactions can simultaneously increase AMPAR- and decrease KAR-mediated synaptic transmission at the same population of synapses.
PUBLISHED
Keywords: Kainate Receptors; PDZ domain-containing proteins; Neuroscience